(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
For an additional aircraft power system, both AC and DC power having high voltage levels are required. with various flight loads. This paper introduces an induction generator based on AC / DC hybrid MEA power generation system. In the proposed system structure, a high-speed generator/generator and a low-speed generator are fitted with high pressure (HP) and low pressure (LP) of the spools of the engine, respectively. In production mode, all alternating AC power is generated by the HP generator while the DC power supply is supplied by both HP and LP generators. The control system is designed to control the AC power supply and direct the DC power supply between the two generators. The proposed AC / DC-based induction generator system results in reduced demand for computer hardware compared to the AC and DC production systems.